THE IMPACT OF MORNING PHYSICS ON HUMAN HEALTH - Akbarova Barchinoy Bakievna; Yuldashev Elmirza Kholmirzaevich; Juraeva Odina Vohobjon kizi; Erkinjonova Sevinch Elmurodjon qizi; Kirgizova Nafisahon Abdullajon kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Deciding on a healthy lifestyle in our society has risen to the level of state policy, and at the same time, fundamental reforms in raising a physically mature and healthy generation are being gradually implemented in our country. For example, the Law of the Republic of Uzbekistan "On Physical Education and Sports" and the Cabinet of Ministers’ Decision "On Measures to Further Develop Physical Education and Sports in Uzbekistan" the intended important tasks have been expressed.